Injectable Click-Crosslinked Hyaluronic Acid Depot to Prolong Therapeutic Activity in Articular Joints Affected by Rheumatoid Arthritis - Seo, Jiyoung; Park, Seung Hun; Kim, Min Ju; Ju, Hyeon Jin; Yin, Xiang Yun; Min, Byoung Hyun; Kim, Moon Suk (ACS Applied Materials and Interfaces, 2019)
The aim of this study was to design a click-crosslinked hyaluronic acid (HA) (Cx-HA) depot via a click crosslinking reaction between tetrazine-modified HA and trans-cyclooctene-modified HA for direct intra-articular injection into joints affected by rheumatoid arthritis (RA). The Cx-HA depot had significantly more hydrogel-like features and a longer in vivo residence time than the HA depot. Methotrexate (MTX)-loaded Cx-HA (MTX-Cx-HA) - easily prepared as an injectable formulation - quickly formed an MTX-Cx-HA depot that persisted at the injection site for an extended period. In vivo MTX biodistribution in MTX-Cx-HA depots showed that a high concentration of MTX persisted at the intra-articular injection site for an extended period, with little distribution of MTX to normal tissues. In contrast, direct intra-articular injection of MTX alone or MTX-HA resulted in rapid clearance from the injection site. After intra-articular injection of MTX-Cx-HA into rats with RA, we noted the most significant RA reversal, measured by an articular index score, increased cartilage thickness, extensive generation of chondrocytes and glycosaminoglycan deposits, extensive new bone formation in the RA region, and suppression of tumor necrosis factor-α or interleukin-6 expression. Therefore, MTX-Cx-HA injected intra-articularly persists at the joint site in therapeutic MTX concentrations for an extended period, thus increasing the duration of RA treatment, resulting in an improved relief of RA.
Keywords: Cartilage thickness; Crosslinking reaction; Intra-articular injection; Long lasting; methotrexate; Rheumatoid arthritis; Therapeutic activity; Tumor necrosis factor alpha; Animals; Arthritis, Rheumatoid; Chondrocytes; Delayed-Action Preparations; Glycosaminoglycans; Humans; Hydrogels; Injections, Intra-Articular; Interleukin-6; Joints; Male; Methotrexate; Mice; Rats; RAW 264.7 Cells; Tissue Distribution; Tumor Necrosis Factor-alpha; click-crosslinking; hyaluronic acid depot; intra-articular injection; long-lasting release; methotrexate; rheumatoid arthritis